Annual variation of strato-mesospheric carbon monoxide measured by ground-based Fourier transform infrared spectrometry - V. Velazco; S. W. Wood; M. Sinnhuber; I. Kramer; N. B. Jones; Y. Kasai; J. Notholt; T. Warneke; T. Blumenstock; F. Hase; F. J. Murcray; O. Schrems (Atmospheric Chemistry and Physics, 2007)
We present long-term time-series of strato-mesospheric CO vertical columns measured from stations located in Antarctica, mid-latitudes and the Arctic, covering the period from 1997–2005. The instrument and the measurement technique allows the separation of tropospheric and strato-mesospheric contributions to the CO column, therefore providing information on the chemistry and dynamics both at low and high altitudes. Data from polar stations show a similar annual variability of strato-mesospheric CO with a strong maximum in late winter and spring. A small enhancement in late summer for some stations, which we call the "summer bulge", can be seen occasionally. Generally, the mid-latitude stations show no significant annual variability of strato-mesospheric CO columns. Measurements were compared with a two-dimensional chemistry-transport model of the middle atmosphere. The annual and latitudinal variations of CO are reproduced well by a model run including thermospheric CO. Comparison with two model scenarios show that the polar winter maximum is due solely to downward transport of thermospheric CO, while CHOx chemistry in the stratosphere could probably contribute to the summer maximum.